2021
DOI: 10.3390/foods10050957
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for the Production of Meat Products with a Low Sodium Chloride Content and Improved Quality Characteristics—A Review

Abstract: In recent years, consumer concerns regarding high levels of sodium chloride (NaCl) intake have increased, given the associated risk of cardiovascular disease. This has led food industries to consider lowering the use of sodium in food products. However, it is well known that the addition of NaCl to meat products enhances their quality, including water-holding capacity, emulsification capacity, juiciness, and texture. Thus, it is difficult to completely remove salt from meat products; however, it is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Our study showed that dietary SK supplementation improved the meat quality of chickens by increasing water holding capacity and decreasing cooking loss. The water holding capacity is known as a determinantal factor of meat quality [ 3 ]. The significantly lower cooking loss in SK-supplemented treatments may be due to the lower serum corticosterone level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that dietary SK supplementation improved the meat quality of chickens by increasing water holding capacity and decreasing cooking loss. The water holding capacity is known as a determinantal factor of meat quality [ 3 ]. The significantly lower cooking loss in SK-supplemented treatments may be due to the lower serum corticosterone level.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous increase in the SD of broiler chickens in the poultry industry to decrease production costs increases health and welfare issues [ 2 ]. In addition to low body weight gain, production of broiler chickens in a high-SD situation decreases meat quality including water-holding capacity and meat tenderness by increasing the oxidative reactions [ 1 , 3 ]. As the traditional broiler’s meat is costly because of higher meat quality compared with modern broilers, the low meat quality can compromise the marketability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 2021 [ 176 ] included irradiation technology among the new technologies, which should extend the shelf life of meat. However, the results of the experiments are controversial, because of undesired sensory changes of the irradiated meat occurring due to the lipid and proteins oxidation.…”
Section: Special Technologiesmentioning
confidence: 99%
“…Various strategies have been developed to improve the sensory properties of meat products. In addition, quality properties or microbial safety of reduced salt meat products have been improved with various strategies hot-boning, high-pressure, radiation, ultrasound, pulsed electric fields, metallic agents, and various natural enhancement and suitable sodium reduction contents are suggested by Kim et al [ 72 ]. In fact, the aforementioned strategies could prevent a decrease in the quality deterioration of meat products.…”
Section: Strategies To Improve the Sensory Properties Of Reduced-salt Meat Productmentioning
confidence: 99%